1999
DOI: 10.3201/eid0503.990308
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Diseases among U.S. Military Personnel: Countering Emerging Threats

Abstract: Emerging respiratory disease agents, increased antibiotic resistance, and the loss of effective vaccines threaten to increase the incidence of respiratory disease in military personnel. We examine six respiratory pathogens (adenoviruses, influenza viruses, Streptococcus pneumoniae, Streptococcus pyogenes, Mycoplasma pneumoniae, and Bordetella pertussis) and review the impact of the diseases they cause, past efforts to control these diseases in U.S. military personnel, as well as current treatment and surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
161
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(171 citation statements)
references
References 55 publications
5
161
3
Order By: Relevance
“…Adenovirus is a common and important pathogen causing acute respiratory disease (ARD) outbreaks in Korean military soldiers. Epidemics of adenovirus-associated ARD have been widely reported among recruits at the US Department of Defense (DoD) training centers (1,19,20). The most common symptoms of adenovirus infections in the present cases were fever and cough, which are in accordance with previous reports (9,20,21).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Adenovirus is a common and important pathogen causing acute respiratory disease (ARD) outbreaks in Korean military soldiers. Epidemics of adenovirus-associated ARD have been widely reported among recruits at the US Department of Defense (DoD) training centers (1,19,20). The most common symptoms of adenovirus infections in the present cases were fever and cough, which are in accordance with previous reports (9,20,21).…”
Section: Discussionsupporting
confidence: 81%
“…Young healthy adults serving in the military are often at an increased risk of respiratory infections (1). Training stressors (2) and crowding (3) facilitate the transmission of respiratory pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, we found rates of ILIs to be 2-16 times higher among the recruits compared to the non-recruits depending on the service, immunization group, analysis cohort, and year of study. Previous studies of the recruit population have reported significant burden of respiratory disease and outbreaks of disease, due primarily to adenovirus, influenza, respiratory syncytial virus, and bacterial infections [14,18,[40][41][42][43]. The high burden and mixing of a variety of respiratory pathogens in this setting may alter the protective effect of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The U.S. military has been a strong proponent for the development and use of influenza vaccines since the 1940s [10]. Annual influenza immunization for the active force began in the 1950s and total force (active and reserve components) influenza immunization remains a mandatory yearly requirement barring a contraindicating condition [10,18]. Continually since the 2003-2004 influenza season, military immunization policies have called for preferential use of LAIV for all eligible service members, with TIV reserved for those not eligible to receive LAIV [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Since termination of Wyeth vaccine production, the burden of adenovirus disease in recruits has increased to that of the pre-vaccine era. Further, a study found that nearly 90% of new recruits were seronegative for either type 4 or 7 adenovirus, and therefore susceptible to adenovirus infection [38,39]. Because of the surge of adenovirus cases, the DoD contracted with Barr Laboratories (now Barr Pharmaceuticals) in September 2001 to develop replacement live types 4 and 7 adenovirus vaccines.…”
Section: Adenovirus Vaccines (Types 4 and 7) And Related Research Effmentioning
confidence: 99%